Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/adma.201400297
|View full text |Cite
|
Sign up to set email alerts
|

Remote Trap Passivation in Colloidal Quantum Dot Bulk Nano‐heterojunctions and Its Effect in Solution‐Processed Solar Cells

Abstract: More-efficient charge collection and suppressed trap recombination in colloidal quantum dot (CQD) solar cells is achieved by means of a bulk nano-heterojunction (BNH) structure, in which p-type and n-type materials are blended on the nanometer scale. The improved performance of the BNH devices, compared with that of bilayer devices, is displayed in higher photocurrents and higher open-circuit voltages (resulting from a trap passivation mechanism).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
78
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 29 publications
(34 reference statements)
4
78
0
Order By: Relevance
“…Great efforts have been put in developing surface passivation approaches to reduce the traps, and power conversion efficiency (PCE) of PbS quantum dot photovoltaics (QDPVs) has been significantly improved (over 10%)12131415. Nevertheless, the achieved PCE is still far below the expected and the surface traps remains a key limiting factor for PbS QDPVs161718.…”
mentioning
confidence: 99%
“…Great efforts have been put in developing surface passivation approaches to reduce the traps, and power conversion efficiency (PCE) of PbS quantum dot photovoltaics (QDPVs) has been significantly improved (over 10%)12131415. Nevertheless, the achieved PCE is still far below the expected and the surface traps remains a key limiting factor for PbS QDPVs161718.…”
mentioning
confidence: 99%
“…We suggested that in the mixed layers, the mid‐gap trap states of the p‐type PbS CQDs are partly filled with electrons donated by the nearby n‐type ZnO or Bi 2 S 3 . This model can further explain the increase of the band‐edge PL of the PbS CQDs when the dots are mixed with ZnO nanoparticles . Overall, remote doping of CQDs by other molecules or nanocrystalline materials, such as metallic nanoparticles, is an interesting concept, however, there are certain factors that limit its use in optoelectronic devices.…”
Section: Doping Schemesmentioning
confidence: 92%
“…The researchers reported that the conductance of the composite films was increased by 100 times compared with the conductance of either of the constituent materials, owing to p‐type doping of the PbTe by the Ag 2 Te crystal phase. We proposed similar doping in the context of explaining the superior electrical characteristics of solar cells that employ bulk nanoheterojunction (BNH) layers of PbS CQDs mixed with ZnO or Bi 2 S 3 nanoparticles . We suggested that in the mixed layers, the mid‐gap trap states of the p‐type PbS CQDs are partly filled with electrons donated by the nearby n‐type ZnO or Bi 2 S 3 .…”
Section: Doping Schemesmentioning
confidence: 99%
“…Since the first reports 1,2 , a dramatic improvement in power conversion efficiency (PCE) has been achieved overpassing 9% with PbS(Se) QDs leading the race as the material of choice 5 . This progress has been underpinned by the design of new heterostructures [5][6][7][8] , improved surface passivation schemes 3,4 and advanced device architectures for more efficient charge collection and suppressed recombination 9,10 . While improvement in PCE of QD solar cells has been thoroughly sought after over the years, the photostability of this technology still remains an open challenge to further increase its technology readiness level, albeit initial promising results on low-performance PbS QD solar cells 11 .…”
Section: Icrea-institució Catalana De Recerca I Estudis Avançats Llumentioning
confidence: 99%